Air rescue and occupational damage for health care professionals: an integrative review (Research, Society and Development, 2022)
This study aimed to identify occupational damage to health professionals who work in air rescue. An integrative review was carried out through research in the data sources: Web of Science, National Library of Medicine, Cumulative Index to Nursing and Allied Health Literature, Scientific Electronic Library Online, Scopus and Virtual Health Library. Controlled descriptors in English and Portuguese were used, indexed in the Health Sciences Descriptors, namely: “Air Ambulances / Air Rescue”; “Health Personnel / Health Professionals”; “Occupational Health / Occupational Health”, carried out during the months of September and October 2021. The associated Boolean operator used was the “AND”. 111 publications were found, of which 83 were excluded after applying the exclusion criteria, leaving 28 publications. After reading titles and abstracts, 18 publications were excluded, of these, 3 were excluded after reading in full, leaving 7. It is noteworthy that, as the main occupational damage for health professionals who work in air rescue, susceptibility to stress, which in turn, it is related to burnout syndrome, linked to few hours of sleep, work overload, excessive and prolonged use of personal protective equipment, exposure to noise above the allowed. Thus, the need to develop more studies focused on the subject in question is evident, given the information corroborated by the literature presented.